THU0621 One Third of Patients with Established Rheumatoid Arthritis (RA) Are Correctly Vaccinated against Influenza and Pneumococcus and This Is Increasing: 3 Year Longitudinal Assessment of 776 Patients. (15th July 2016) - Gossec, L.; Molto, A.; Foissac, F.; Fayet, F.; Mouterde, G.; Gaudin, P.; Soubrier, M.; Dougados, M.; ,
Abstract : Background: Influenza and pneumococcal vaccinations are recommended in all patients with RA. However, it is well known that a gap exists between recommendations and their implementation in real life. Objectives: As EULAR recommendations for vaccinations are now widely disseminated, we took the opportunity of assessing vaccination rates of the patients who participated in the COMEDRA study [1], both at study entry and 3 years after the trial ended, to assess the progression of vaccination rate in this long-standing RA population undergoing a nurse-led program. Methods: This was an open long term (3 years) extension of the COMEDRA 6 month randomized controlled trial in which patients with definite, stable RA were visiting a nurse for comorbidity counselling. Vaccination status was assessed during the RCT and nurses provided advice on vaccinations, and again 3 years later, during a face-to-face interview with a nurse. Agreement with the vaccination recommendations was defined as (a) influenza vaccination performed within the last 12 months and (b) pneumococcal vaccination performed within the last 5 years. The proportion of patients in accordance with the recommendations was compared between baseline and 3-year assessment using a McNemar test for paired data. The probability to be in accordance with recommendations was assessed by logistic mixed models including in the model the patient as random effect and as fixed effects: age, gender, disease duration, DAS28, educational level, work status, any biologic at baseline, and trial group and centre. Results: Of the 970 recruited patients, 776 (80%) were followed up at 2–4 years and 759 (78%) had available data regarding both influenza and pneumococcal vaccination status: mean (±sd) age 61 (±11) years, median [IQR] disease duration 15 [10–23] years; 607 (80%) were women and 81% had ever received a biologic. The mean baseline and 3-year DAS28 scores were respectively 2.99±1.30 and 2.83±1.34. At baseline, 337 (44.4%), 459 (60.5%) and 252 (33.2%) patients were in agreement with recommendations for influenza, pneumococcal and both vaccinations, respectively. After 3 years, this agreement increased for both vaccinations, to 420 (55.3%), 499 (65.7%) and 317 (41.8%) respectively (Table 1 ). Having ever received a biologic (odds ratio, OR=4.73 [95% CI: 2.62–8.52]), centre size (OR=2.8 [1.04–1.7]), university education (OR=1.79 [1.11–2.89]) and higher age (OR=1.07 [1.04–1.10]), were independently associated with being in accordance with both vaccinations recommendations. Conclusions: The agreement with the EULAR vaccination recommendations is moderate but has increased in patients who had participated in a nurse-led program aiming at checking systematically for vaccination status. References: Dougados M, Soubrier M, et al. Ann Rheum Dis. 2015;74(9):1725–33. Acknowledgement: grant from the French National Research Program (PHRC AOM 12072). Disclosure of Interest: None declared